A means of assessing maximal oxygen intake. Correlation between field and treadmill testing - Cooper, K. H. (JAMA, 1968)
One hundred and fifteen US Air Force male officers and airmen were evaluated on a 12-minute field performance test and on a treadmill maximal-oxygen-consumption test. The correlation of the field-test data with the laboratory-determined oxygen-consumption data was 0.897. The significance of this relationship makes it possible to estimate with considerable accuracy the maximal oxygen consumption from only the results of the 12-minute performance test. This test is readily adaptable to large groups, requires minimum equipment, and appears to be a better indicator of cardiovascular fitness than the more commonly accepted 600-yard run. Because of the high correlation with maximal oxygen consumption, it can be assumed that the 12-minute field performance test is an objective measure of physical fitness reflecting the cardiovascular status of an individual.